Combination Measles-Mumps-Rubella-Varicella Vaccine in Healthy Children: A Systematic Review and Meta-analysis of Immunogenicity and Safety. Issue 44 (November 2015) - Ma, Shu-Juan; Li, Xing; Xiong, Yi-Quan; Yao, A.-.ling; Chen, Qing
Abstract : Abstract: A combined measles-mumps-rubella-varicella (MMRV) vaccine is expected to facilitate universal immunization against these 4 diseases. This study was undertaken to synthesize current research findings of the immunogenicity and safety of MMRV in healthy children. We searched PubMed, Embase, BIOSIS Previews, Web of Science, Cochrane Library, and other databases through September 9, 2014. Eligible randomized controlled trials (RCTs) were selected and collected independently by 2 reviewers. Meta-analysis was conducted using Stata 12.0 and RevMan 5.3. Twenty-four RCTs were included in qualitative synthesis. Nineteen RCTs compared single MMRV dose with measles-mumps-rubella vaccine with or without varicella vaccine (MMR + V/MMR). Similar seroconversion rates of these 4 viruses were found between comparison groups. There were comparable geometric mean titers (GMTs) against mumps and varicella viruses between MMRV group and MMR + V/MMR group. MMRV group achieved enhanced immune response to measles component, with GMT ratio of 1.66 (95% confidence interval [CI] 1.48, 1.86; P  < 0.001) for MMRV versus MMR and 1.62 (95% CI 1.51, 1.70; P  < 0.001) for MMRV versus MMR + V. Meanwhile, immune response to rubella component in MMRV group was slightly reduced, GMT ratios were 0.81 (95% CI 0.78, 0.85; P  < 0.001) and 0.79 (95% CI 0.76, 0.83; P  < 0.001), respectively. Well tolerated safety profiles were demonstrated except higher incidence of fever (relative risks 1.12–1.60) and measles/rubella-like rash (relative risks 1.44–1.45) in MMRV groups. MMRV had comparable immunogenicity and overall safety profiles to MMR + V/MMR in healthy children based on current evidence.